Analisis Kesesuaian Indikator Kualitas Audit Indonesia Dengan Kerangka Kerja Kualitas Audit Dari International Auditing And Assurance Standards Board (IAASB) - Giovani, Marshella; Sheren, Sheren; Tio Pratama, Vincent (CV. Lafadz Jaya, 2023)
Audit quality indicators play an important role in maintaining quality during the audit process, with audit quality indicators minimizing violations or fraud. Indonesia uses audit quality indicators published by the Indonesian Association of Certified Public Accountants (IAPI) in accordance with the IAASB International Auditing and Assurance Standards Board (IAASB) audit quality indicators. The method applied in this study is a qualitative descriptive method using secondary data. The results of the study show that IAPI has implemented and adopted several parts of the audit quality framework set by the IAASB. On the other hand, there are several items that are only owned by IAPI itself, such as the span of control of the engagement and the policy of compensation for services.